Antimicrobial membranes based on polycaprolactone:pectin blends reinforced with zeolite faujasite for cloxacillin-controlled release - Bárbara Bernardi; João Otávio Donizette Malafatti; Ailton José Moreira; Andressa Cristina de Almeida Nascimento; Juliana Bruzaca Lima; Lilian Aparecida Fiorini Vermeersch; Elaine Cristina Paris (Discover Nano)
Abstract Multifunctional membranes applied to biomedical materials become attractive to support the biological agents and increase their properties. In this study, biopolymeric fibers based on polycaprolactone (PCL) and pectin (PEC) were reinforced with faujasite zeolite (FAU) for cloxacillin antibiotic (CLX) loading. FAU with a high specific surface area (347 ± 8 m2 g−1), high crystallinity and particles with a diameter of up to 100 nm were produced under optimized synthesis conditions (100 °C/4 h). Zeolites were incorporated into polymeric nanofibers to be a cloxacillin (CLX) carrier in wound treatment, using electrospinning as an efficient synthesis method. The fibers produced showed good mechanical resistance and the incorporation of CLX was proven by assays to inhibit the growth of Staphylococcus aureus bacteria. The controlled release of CLX in different pH conditions, which simulate the wound environment, was carried out for up to 229 h, achieving a released CLX concentration of up to 6.18 ± 0.02 mg L−1. These results prove that obtaining a hybrid fiber (polymer-zeolite) to incorporate drugs to be released in a controlled manner was successfully achieved. The bactericidal activity of this material shows that its use for measured applications could be an alternative to conventional methods. Graphical abstract